2020
DOI: 10.1007/s11104-020-04557-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Composition of Sunlight Affects the Microbial Functional Structure of Beech Leaf Litter During the Initial Phase of Decomposition

Abstract: Aims This study tests whether different spectral regions of sunlight affect the microbial decomposer assemblage in surface leaf litter in a beech understorey over the first 6 months following leaf senescence. Methods We performed a litterbag experiment employing filters attenuating combinations of UV-B, UV-A, blue, and green light as well as the whole spectrum of sunlight. We measured changes in microbial biomass and community structure, litter mass loss and litter chemistry during the first 6 months of decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…With regards to the difference observed in the AWCD patterns between sampling environments (i.e., outside and inside the cave), the microbial communities found outside of the cave were highly metabolically active, consuming and up taking carbon from the environment to fuel catabolic activity during cell growth. Previous studies have also reported that, in terrestrial environments, sunlight is the most influential factor for the production of simple organic carbon via photodegradation, resulting in a higher metabolic activity in microorganisms [ 35 , 36 ]. Similarly, in a study on permafrost, another extreme environment, the authors found that sunlight exposure can enhance the microbial respiration rate up to >40% compared with dark areas, mediated by dissolved organic carbon [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the difference observed in the AWCD patterns between sampling environments (i.e., outside and inside the cave), the microbial communities found outside of the cave were highly metabolically active, consuming and up taking carbon from the environment to fuel catabolic activity during cell growth. Previous studies have also reported that, in terrestrial environments, sunlight is the most influential factor for the production of simple organic carbon via photodegradation, resulting in a higher metabolic activity in microorganisms [ 35 , 36 ]. Similarly, in a study on permafrost, another extreme environment, the authors found that sunlight exposure can enhance the microbial respiration rate up to >40% compared with dark areas, mediated by dissolved organic carbon [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…outside and inside the cave), the microbial communities found outside of the cave were highly metabolically active, consuming and up taking carbon from the environment to fuel catabolic activity during cell growth. Previous studies have also reported that, in terrestrial environments, sunlight is the most in uential factor for the production of simple organic carbon via photodegradation, resulting in a higher metabolic activity in microorganisms [33,34]. Similarly, in a study on permafrost, another extreme environment, the authors found that sunlight exposure can enhance microbial respiration rate up to > 40% compared to dark areas, mediated by dissolved organic carbon [35].…”
Section: Discussionmentioning
confidence: 87%
“…Herbaceous and shrub litter lost mass much faster than tree litter, irrespective of the filter treatment in the understorey (Fig. S6), attributable to their low toughness and low C and lignin content (Table S1), which are structural and persistent compounds affecting decomposability (Pieristè et al ., 2020a,b). In contrast, tougher litter from trees with a high content of recalcitrant compounds is more prone to photodegradation once exposed to sunlight in the gap (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the solar radiation reaching the forest floor varies greatly, as forests undergo succession, displaying spatially and temporally dynamic canopy and soil processes. In deciduous forest understoreys, seasonal canopy phenology causes large changes in light quality and irradiance through the year that potentially produce complex effects on litter decompostion (Pieristè et al ., 2019, 2020a,b). Canopy gap dynamics created by a variety of natural or human disturbances (Čada et al ., 2016), produce heterogeneous light environments in a forest that partially drive species diversity (Wang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation